Use of Produced Cell-Free Supernatant Antibacterial Produced by Pediococcus pentosaceus BAF715 as Biopreservative of Buffalo Meatballs at Cold Temperatures - Afriani, Afriani; Azis, Abdul; Elymaizar, Zulfa; Ahzara, Yulia Rizka; Iskandar, Hidayat (Jurnal Sain Peternakan Indonesia, 2024)
Meatballs are a processed-meat product which has high nutritional value and is classified as perishable food products. Therefore, preservative agents were needed to maintain the shelf life of meatball products. Natural preservative agents that can be used are antibacterial compounds derived from lactic acid bacteria. The objective of this study was to determine the use of cell-free supernatant antibacterial produced by Pediococcus pentosaceus BAF715 as a biopreservative of buffalo meatballs storage in cold temperatures. Buffalo meatballs were soaked in cell-free supernatant antibacterial for 30 minutes, then stored at cold temperatures for 0, 3, 6, 9, and 12 days were used as treatments. The results showed that the storage time of meatballs soaked in cell-free antibacterial supernatant can reduce the total bacteria, Staphylococcus aureus and kill Escherichia coli. The storage time can maintain pH and percentage of free water. Total bacteria and Staphylococcus aureus in 9 days of storage and it still within the requirements of the Indonesian National Standard (SNI 3818: 2014) regarding the quality of meatballs, while control meatballs (without soaked) were only up to 3 days of storage. It was concluded that the cell-free supernatant antibacterial produced by Pediococcus pentosaceus BAF715 was able to maintain the microbiological and physical quality of buffalo meatballs until 9 days of storage at cold temperatures.